Derivatization, molecular docking and in vitro acetylcholinesterase inhibitory activity of glycyrrhizin as a selective anti-Alzheimer agent. Issue 18 (17th September 2019) - Abdel Bar, Fatma M.; Elimam, Diaaeldin M.; Mira, Amira S.; El-Senduny, Fardous F.; Badria, Farid A.
Abstract: Acetylcholinesterase inhibitors (AChE-Is) increase both level and duration of action of acetylcholine (ACh); thus, alleviate symptoms of Alzheimer's disease (AD). Glycyrrhizin, is the main active compound in liquorice root. Its aglycone, glycyrrhetinic acid, has shown several beneficial pharmacological activities. This study reports the synthesis and screening of a series of glycyrrhetinic acid analogs as AChE-Is. Fourteen derivatives were prepared, of which five derivatives are recorded as new viz., 3-phenyl-carbamoyl-18β-glycyrrhetinic acid (J9 ), 3-acetyl-18β-glycyrrhetinic-30-anilinamide (J10 ), 3-acetyl-18β-glycyrrhetinic-30-ethanolamide (J11 ), 3-acetyl-18β-glycyrrhetinic-30- n -butylamide (J12 ) and 18β-glycyrrhetinic acid-30-prenyl ester (J14 ), in addition to nine known derivatives (J1 -J8 &J13 ). CompoundsJ12, J11, J0 andJ3 showed remarkable AChE-I activity with IC50 values of 3.43, 5.39, 6.27 and 8.68 μM, respectively. These results are in full agreement with the docking study. The active compounds were non-cytotoxic to normal cells (WI-38). Abstract :